VD_FINDINFO PC 5/12 - 13/2012 vom 21. Mai 2012 - VD Tribunal cantonal (2012)
LOI FÉDÉRALE SUR LES PRESTATIONS COMPLÉMENTAIRES À L'AVS ET À L'AI, REVENU HYPOTHÉTIQUE | 11 LPC, 4 al. 1 let. c LPC, 9 LPC, 14a al. 1 OPC-AVS/AI, 14a al. 2 OPC-AVS/AI